Προδρομική διόρθωση μηνιαίων δεδομένων σε δεδομένα μηνών ίσης διάρκειας - Δημολιάτης Γιάννης; Μπαλτζής Σωκράτης; Κατσουγιαννόπουλος Βασίλειος (SPOUDAI Journal of Economics and Business, 1999)
The conventional division of the calendar year in 12 months of unequal duration, 31, 30 and 28 (or 29) days, inserts into time-series of monthly data conventional seasonal variations (CSV), which disfigure the true seasonal pattern. There are different methods of retrospective adjustment of the already published monthly data in data of equal durated months. This present study proposes a new, accurate, simple and easy applicated method of prospective data adjustment, directly from the Statistical Services, so to be published as adjusted. It is about 12 simple equations which can be easily applied if there are available daily (and more accurate hourly) data.